Remarkable Thermal Contraction in Small Size Single-Walled Boron Nanotubes (Communications in Computational Physics, 2014)
Density functional theory combined with the Grüneisen approximation isused to calculate the thermal properties of single-walled boron nanotubes (BNTs). Thespecific heat and thermal expansion are investigated. The thermal expansion coefficient of the BNT is found to be significantly correlated with tube size and chirality. Aremarkable thermal contraction is found at small tube diameters. These results indicate that BNTs would have potential applications in sensors, actuators, and memorymaterials.